ANALISIS TINGKAT KESEJAHTERAAN PETANI DI KUBU RAYA - B01107079, Leo Trio Putra Prandana Putra Prandana (Jurnal Pembangunan dan Pemerataan, 2015)
ABSTRACTThe purpose of this study was to determine and analyze the level of welfare of farmers isbased on the development of farmers' income in Kubu Raya, to determine and analyze thelevel of welfare of farmers by spending Food Farmers in Kubu Raya and to identify andanalyze the level of welfare of farmers based on exchange Farmers in Kubu Raya, Themethodology used descriptive methodThe findings regarding the performance of welfare of farmers in this study are describedon the household income level of farmers, the proportion of household food expenditure,farmers exchange rate generally indicates the degree pretty good. The agricultural sector stillplays an important role in contributing to the household income in Kubu Raya. Kubu Raya inthe last 2 years (2012-2013) contribution dropped. Household food consumption expenditureof farmers in the two districts have not been good, where the proportion of food expenditurereaches 59.5 to 62.4 percent of total household expenditure. This condition indicates that thelevel of welfare of rice farmers in Kubu Raya has not been prosperous. Performance Exchangeassessment Farmers in nine locations on two (2) years of study ranged from 99.37 to 108. Thiscondition indicates that the level of welfare of rice farmers in nine districts of this districtincludes quite good. Based on the performance indicators of the welfare of farmers in 2012and 2013 at nine locations in general studies indicate a fairly good degree.Recommendation that the author gave the need for the government, realizing thepolicies that can encourage agricultural commodities that were examined can be furtherdeveloped, including through subsidized supply of means of production as well as marketingdevelopment and the need for the development strategy of agriculture (food), which may beproposed in the study area is the development of a commodity in accordance with the potentialof the location. In fact, agricultural commodities studied, its existence is not evenly distributedin all locations, but only at certain locations as appropriate. Such conditions provide strategicdirection in order to make Agropolitan in locations suitable for the development of thecommodity in question.Keywords: Welfare, Revenue, Expenditure Farmers.